Understanding and modifying Fabry disease: Rationale and design of a pivotal Phase 3 study and results from a patient-reported outcome validation study - Wanner, Christoph; Kimonis, Virginia; Politei, Juan; Warnock, David G.; Üçeyler, Nurcan; Frey, Aline; Cornelisse, Peter; Hughes, Derralyn (Molecular genetics and metabolism reports, 2022)
The use of available treatments for Fabry disease (FD) (including enzyme replacement therapy [ERT]) may be restricted by their limited symptom improvement and mode of administration. Lucerastat is currently being investigated in the MODIFY study as oral substrate reduction therapy for the treatment of FD. By reducing the net globotriaosylceramide (Gb3) load in tissues, lucerastat has disease-modifying potential to improve symptoms and delay disease progression. MODIFY is a multicenter, double-blind, randomized, placebo-controlled, parallel-group Phase 3 study (ClinicalTrial.gov: NCT03425539); here we present the rationale and design of this study. Eligible adults with a genetically confirmed diagnosis of FD and FD-specific neuropathic pain entered screening. Patients were randomized (2:1) to receive either oral lucerastat twice daily or placebo for 6 months; treatment allocation was stratified according to sex and ERT treatment status. The main objectives of MODIFY are to assess the effects of lucerastat on neuropathic pain, gastrointestinal (GI) symptoms, FD biomarkers, and determine its safety and tolerability. Neuropathic pain and GI symptoms are key features of FD that have a significant impact on quality of life. Despite various tools available to assess pain and GI symptoms, there are currently limited tools available to assess neuropathic and GI symptoms in FD, validated according to health authority guidelines. Based on FDA recommendations, we undertook a patient-reported outcome (PRO) validation study, using a novel eDiary-based PRO tool to assess the validity of evaluating neuropathic pain as a primary efficacy endpoint in MODIFY. Results from the PRO validation study are included. To date, MODIFY is the largest Phase 3 clinical study conducted in patients with FD. Enrollment to MODIFY is now complete, with 118 patients randomized. Results will be presented in a separate publication. Long-term effects of lucerastat are being assessed in the ongoing open-label extension study (NCT03737214). •There remains a need for treating patients with Fabry disease.•MODIFY investigated lucerastat as substrate reduction therapy for Fabry disease.•Limited tools are available to assess neuropathic and GI symptoms in Fabry disease.•MODIFY assessed neuropathic pain and GI symptoms as primary and secondary efficacy endpoints.•MODIFY used FDA-recommended validated tools for primary and secondary efficacy endpoints.